Improving the Quality of Hindu Education in the Era of Society 5.0 through Digital Culture - Ni Putu Eka Merliana; Ni Nyoman Tantri (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
The concept of society 5.0 is one of the factors required to innovate the development of digital technology adapted to the needs of people's lives, in which the role of innovation will bring up new technology. Utilizing technology produces a digital culture that is applied in everyday life. The importance of quality of education at this time makes especially Hindu educational institutions, must continue to innovate and strategy with the use of technology. Improving the quality of Hindu education can be influenced by using technology as a form of digital culture by not forgetting Hindu religious norms. This is the reason for reviewing in looking for digital cultural factors to improve the quality of Hindu education. This paper uses a descriptive qualitative method with a literature review type of research. This quality improvement cannot be separated from the role of technology in the era of society 5.0, so the change towards digital culture will make it easier for Hindu educational institutions to improve the quality of Hindu education by not being separated from the factors of the digital culture.